Impact of gynecological operations on sleeping and emotion disorders in women in peri and postmenopausal age (Menopause Review/Przegląd Menopauzalny, 2011)

(untitled) - Wilczak, Maciej; Mojs, Ewa; Samulak, Dariusz; Michalska, Magdalena Monika; Ziarko, Michał; Kaczmarek, Łukasz
Sleeping and emotion disorders, especially insomnia and sleep continuity disorders, are most severely felt and determine women’s everyday life. The research was aimed at assessing the dependence of the occurrence of sleeping and emotion disorders in women of perimenopausal age and the use of hormonal replacement therapy. 86 women participated in the study. The patients were between 23 and 70 years of age (M = 51,07; SD = 12,75). They were recruited from gynaecological wards in the Wielkopolska region. They underwent surgical interventions by endoscopy and per vagina method also. In the study standardized test methods of determined reliability and internal accuracy were used: Courtauld Emotional Control Scale (CECS), Epworth Sleepiness Scale, Athens Insomnia Scale, Stanford Sleepiness Scale, Beck Depression Inventory, Satisfaction With Life Scale, Multidimensional Self-Esteem Inventory. The results show there was the negative correlation between satisfaction with life and the level of state anxiety (r-Person = –0,40; p < 0,01), depression (r-Person = –0,37; p < 0,01) and insomnia (r-Person = –0,39; p < 0,01). Young women in the premenstrual period present ed higher levels of emotion control [F(2,55) = 4,193; p < 0,05], the acceptance of disease [F(2,55) = 18,106; p < 0,01], and reported insomnia symptoms less frequently [F(2,55) = 13,830; p < 0,01].